2021
DOI: 10.3390/su132413895
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emission Estimation of Oil and Gas Sector: A Review of Measurement Technologies, Data Analysis Methods and Uncertainty Estimation

Abstract: The emission estimation of the oil and gas sector, which involves field test measurements, data analysis, and uncertainty estimation, precedes effective emission mitigation actions. A systematic comparison and summary of these technologies and methods are necessary to instruct the technology selection and for uncertainty improvement, which is not found in existing literature. In this paper, we present a review of existing measuring technologies, matching data analysis methods, and newly developed probabilistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Infrared visualization, a predominant method, detects gases by observing light intensity variations due to gas absorption in the infrared spectrum, a passive sensing approach . The imagery, sequenced into videos, is analyzed by continuous monitoring companies along with their collected meteorological data to identify emissions and estimate the emissions rate …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared visualization, a predominant method, detects gases by observing light intensity variations due to gas absorption in the infrared spectrum, a passive sensing approach . The imagery, sequenced into videos, is analyzed by continuous monitoring companies along with their collected meteorological data to identify emissions and estimate the emissions rate …”
Section: Methodsmentioning
confidence: 99%
“…16 The imagery, sequenced into videos, is analyzed by continuous monitoring companies along with their collected meteorological data to identify emissions and estimate the emissions rate. 38 Participants were given the option to evaluate detection performance (reporting binary 0−1 data corresponding to whether gas is emitting) or both detection and quantification performance (reporting the estimated rate of emission in kilograms per hour). It is important to note that the Stanford team did not participate in the analysis of the reports submitted by the teams.…”
Section: Acs Esandt Airmentioning
confidence: 99%
“…16 The imagery, sequenced into videos, is analyzed by continuous monitoring companies along with their collected meteorological data to identify emissions and estimate the emissions rate. 38 Participants were given the option to evaluate detection performance (reporting binary 0-1 data corresponding to whether gas is emitting), or both detection and quantification performance (reporting the estimated rate of emission in kilograms per hour). It is important to note that the Stanford team did not participate in the analysis of the reports submitted by the teams.…”
Section: Description Of Technologies Testedmentioning
confidence: 99%
“…In a comparative review conducted in 2021, Sun et al, 9 investigated how CH 4 emissions estimation technologies, data analysis, and probabilistic tools for emission uncertainty estimation unite to form an efficient system of CH 4 management for the ONG energy sector. The authors found that spatial scale was a primary factor in selecting CH 4 emission measurement technology where bottom-up or top-down methods were applied to calculate emission rates from CH 4 concentrations.…”
Section: Literature Reviewmentioning
confidence: 99%